Keragaman Serangga di Pola Pertanaman Tumpang Sari Kedelai-Titonia - Putri Mustika Sari; Adriansyah Yoesoep; Lisdayani Lisdayani (Universitas Sebelas Maret, 2021)
Plants that have a wide range of insect presence, decreased insect diversity and abundance were so few consequenced because the absence of one insect species can be replaced by the presence of another. The bad consequences that occur are the types of plants that have specific insect specificities because the absence of these insects will cause the failure of plant pollination and will directly cause a decrease in crop production. This study aimed to determine the diversity of insect species that come in the soybean-tithonia intercropping. The method was used direct observation in tithonia-soybean intercropping, took insects using a sweep net in the morning. The results showed that there were 15 types of insects identified, namely Epilachna sp.; Coccinella sexmaculata; Coccinella transveralis; Verania lineata; Ropalidia fasciata; Priocnemis sp.; Naupactus leucoloma; Piezodorus guildinii; Bemicia tabaci; Agromyza phaseoli; Spodoptera sp.; Nezara viridula; Paederus fusipes; Hylaeus sp.; and Trigona sp. The range of results of the calculation of the diversity index showed that the five treatments in intercropping plants had the same abundance. So it was needed to calculate the highest diversity index value or maximum H expressed in Ln S. The maximum H value in this study is 2.708, which is a measure of moderate species diversity (1<H’<3).